Immunohistochemical study of the expression of N-cadherin in cutaneous melanoma and in dysplastic melanocytic nevi - Murtas, Daniela; Piras, Franca; Maxia, Cristina; Minerba, Luigi; Ferreli, Caterina; Pilloni, Luca; Diana, Andrea; Sirigu, Paola; Perra, Maria (Italian Journal of Anatomy and Embryology, 2015)
It has been suggested that the invasive and metastatic potential of melanoma cells reflects their ability to undergo epithelial-mesenchymal transition (EMT)-like phenotypic changes (1). Important hallmarks of EMT include the loss of E-cadherin expression and increased expression of the cell adhesion molecule N-cadherin. This cadherin switch leads melanoma cells to lose contact with keratinocytes in the epi- dermis and interact instead with stromal fibroblasts and endothelial cells, thus promoting dermal and vascular melanoma invasion (2). In melanoma, up-regulation of N-cadherin can be induced by the overexpression of the transmembrane receptor Notch1, thus providing a mechanism that underlines increased melanoma cell adhesion, survival, growth, and tumor progression when Notch signaling is activated (3). In this study, the expression of N-cadherin and Notch1 was evaluated by immuno- histochemical analysis in primary cutaneous melanomas and lymph node metastases. First, we evaluated the prognostic impact of high N-cadherin expression on sur- vival in melanoma patients. Second, we correlated the expression of N-cadherin with the full clinicopathological data of patients. Third, we investigated the relationship between the expression of N-cadherin and Notch1. Moreover, N-cadherin expression was evaluated in dysplastic melanocytic nevi and in normal skin. The results will be discussed.